The Effect of Group Guidance Services in Increasing Self Confidence for Madrasah Students Through Group Discussion Techniques - Dahniar Ritonga; Abdul Aziz Rusman (Edumaspul: Jurnal Pendidikan, 2024)
This article aims to find out the influence of group guidance services in increasing the self-confidence of madrasah students through group discussion techniques. This research uses the quantitative research method OneGroup Pretest-Posttest Design Experiment. In the validity and reliability test of the 30 statement items in the form of a selfconfidence scale created by the researcher, there were 24 statement items that were valid for use with the results being said to be valid if the calculated r was > from r table with the r table value at the 5% significance level being 0.2787. In the reliability test, Cronbrach alpha data was obtained with a Cronbroach Alpha value greater than 0.05 (0.759 > 0.05). The population in this study were all class VIII students of Madrasah Tsanawiyah Islamiyah Gunting Saga with a total of 60 students with a sample of 10 students, all of whom had a low sense of self-confidence and were participants in this research. In sampling, the researcher used a purposive sampling technique, namely a sample selection method with predetermined criteria, which was the chosen sampling strategy. Data analysis was carried out using the Wilcoxon Signed Ranks Test, and the results showed that the significance value was asymp. Sig(2-tailed) ≤ of 0.05, namely 0.005. Based on research that has been conducted, the self-confidence of class VIII students at Madrasah Tsanawiyah Islamiyah Gunting Saga can be increased through group guidance services using discussion techniques which have shown significant results.